DECaPS and SMA Discovery of a Highly Inclined Class I Young Stellar Object with an Outflow: IRAS 08235–4316 - Joshua Bennett Lovell; Kristina Monsch; Garrett K. Keating; David J. Wilner; Gordian Edenhofer; Mark Gurwell; Ramprasad Rao (The Astronomical Journal)
We present images of IRAS 08235–4316 with the Dark Energy Camera Plane Survey (DECaPS; spanning 0.398–1.034 μ m, at ∼1″ resolution) and the Submillimeter Array (SMA; at 1.38 mm (217 GHz) and ∼1 $\mathop{.}\limits^{^{′′} }$ 9 × 1 $\mathop{.}\limits^{^{′′} }$ 2 resolution), a young stellar object (YSO) located in the Vela constellation near to the Puppis boundary, detected in a systematic search for new large/extended emission sources. The DECaPS data show an asymmetric bipolar morphology with a large angular extent of ∼7 $\mathop{.}\limits^{^{′′} }$ 1 separated by a dark lane, characteristic of highly inclined protoplanetary disks and less-evolved YSOs with outflows. The SMA data show an extended continuum structure along the optical dark lane with a smaller angular extent of ∼4 $\mathop{.}\limits^{^{′′} }$ 6. The detected ^12 CO J = 2–1 emission tentatively shows a velocity gradient along the position angle of the dark lane/millimeter continuum, which may trace rotating gas. Additional ^12 CO emission is present, which could trace infalling/outflowing gas and/or a nearby gas cloud. We estimate a distance to IRAS 08235–4316 of at least ∼191 pc. Supported by additional spectral energy distribution modelling, we infer IRAS 08235–4316 to be a newly discovered Class I YSO with an outflow, host to an embedded protoplanetary disk, with a large millimeter radius of ∼440 au and dust mass ≳ 11 M _⊕ .